Lithium deposition redirection mixed conductor layer and preparation method thereof and lithium metal battery
Patent Information
- Application Number
- CN202611087796.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-22
AI Technical Summary
[0007]本发明的目的在于提供一种锂沉积重定向混合导体层及其制备方法和锂金属电池,旨在解决现有硫化物固态锂金属电池中负极侧锂金属易在固态电解质/负极界面处沉积,进而导致枝晶生长、微短路、物理不可逆锂增加、负极库伦效率降低以及循环稳定性不足的问题
1、本发明将传统导电界面层转化为具有电子阻尼、锂离子交换和合金化沉积受体功能的混合导体层,避免单纯高电子导电碳层导致锂金属在硫化物固态电解质侧优先沉积的问题。
Smart Images

Figure CN122599439B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state lithium metal battery technology, and in particular to a lithium deposition redirected hybrid conductor layer, its preparation method, and a lithium metal battery. Background Technology
[0002] With the increasing demands for energy density and safety in power batteries and energy storage devices, solid-state lithium batteries, which use solid electrolytes to replace traditional liquid electrolytes, have attracted widespread attention. Solid-state electrolyte systems help reduce safety risks such as leakage, combustion, and thermal runaway associated with liquid electrolytes, and also enable the application of lithium metal anodes and anode-free battery structures.
[0003] Among various solid-state electrolyte systems, sulfide solid-state electrolytes have become an important candidate system for solid-state lithium metal batteries due to their high room-temperature lithium-ion transport capacity, good compaction properties, and low interfacial contact impedance. However, the interfacial stability between the sulfide solid-state electrolyte and the lithium metal anode remains insufficient. During charge and discharge, if lithium metal preferentially deposits on the side closer to the sulfide solid-state electrolyte layer, the newly formed lithium metal will directly act on the solid-state electrolyte interface, easily inducing problems such as local stress concentration, dendrite growth, interfacial side reactions, and micro-short circuits.
[0004] To improve lithium deposition behavior on the negative electrode side, various interface control methods have been proposed in existing technologies, such as setting up a carbon-based conductive framework, introducing lithiophilic components, constructing an alloyed interface layer, or using a metal / carbon composite layer. However, most existing solutions still focus on reducing nucleation overpotential, improving lithiophilicity, or enhancing electron conductivity. Their control focus is usually on the conductivity, lithiophilicity, or local nucleation behavior of the material itself, rather than the distribution of deposition sites in the thickness direction of the interface layer.
[0005] The failure of the anode interface in sulfide solid lithium metal batteries is not solely due to insufficient interfacial electronic conductivity or lithiophilicity, but is closely related to the spatial matching between electron transport, lithium-ion transport, and deposition acceptor sites along the thickness of the interfacial layer. When electron transport paths, lithium-ion transport paths, and deposition nucleation sites lack a reasonable distribution within the interfacial layer, lithium metal may still preferentially deposit near the sulfide solid electrolyte layer, leading to dendrite growth, micro-short circuits, and physically irreversible lithium accumulation.
[0006] Therefore, it is necessary to provide a hybrid conductor layer for redirecting lithium deposition sites. This hybrid conductor layer should not only improve the conductivity or lithiophilicity of the material, but should also enable spatial matching of electron transport, lithium ion transport, and alloying deposition sites between the sulfide solid electrolyte layer and the negative electrode current collector, so that the lithium metal deposition sites are shifted from the side closer to the sulfide solid electrolyte layer to the side closer to the negative electrode current collector. Summary of the Invention
[0007] The purpose of this invention is to provide a lithium deposition redirected hybrid conductor layer and its preparation method, as well as a lithium metal battery, aiming to solve the problems in existing sulfide solid lithium metal batteries where lithium metal on the negative electrode side is prone to deposition at the solid electrolyte / negative electrode interface, leading to dendrite growth, micro-short circuits, increased physically irreversible lithium, reduced negative electrode coulombic efficiency, and insufficient cycle stability.
[0008] The core of this invention lies not in simply combining carbon materials and alloying metals, but in constructing a hybrid conductor layer that simultaneously functions as an electron damper, lithium-ion exchanger, and alloy deposition acceptor. This hybrid conductor layer modulates electron transport intensity and improves lithium-ion exchange with the sulfide solid electrolyte through an oxidized carbon-based conductive framework. It provides controllable lithium deposition sites through alloy deposition acceptor components, enabling a spatial matching relationship between electron transport, lithium-ion transport, and alloy deposition sites along the layer thickness direction. This induces preferential deposition of lithium metal on the side closest to the negative electrode current collector.
[0009] The technical solution adopted in this invention is as follows: The present invention proposes a lithium deposition redirection hybrid conductor layer for use between a sulfide solid electrolyte layer and a negative electrode current collector; the hybrid conductor layer comprises an oxidized modified carbon-based conductive framework and an alloyed deposition acceptor component; The oxidized carbon-based conductive framework contains oxygen-containing functional groups. The alloyed deposition acceptor component includes one or more of Ag, In, Zn, Sn, and Al, and / or an oxide, fluoride, chloride, or sulfide of at least one of Ag, In, Zn, Sn, and Al; the alloyed deposition acceptor component is generated in an oxidized carbon-based conductive framework through oxygen-containing functional group coordination anchoring, in-situ reduction, or in-situ transformation. The oxidized carbon-based conductive framework and the alloyed deposition acceptor components form a spatially matched structure for electron transport, lithium-ion transport, and alloyed deposition sites in the thickness direction of the mixed conductor layer.
[0010] Furthermore, the carbon-based conductive framework includes one or more of conductive carbon black, carbon nanotubes, graphitized carbon, porous carbon, hard carbon, soft carbon, graphene, and carbon fiber.
[0011] Furthermore, the conductive carbon black includes one or more of the following: ultra-high conductivity carbon, super carbon black, Ketjen black, Cabot conductive carbon, and multi-walled carbon nanotubes.
[0012] Furthermore, the oxygen-containing functional group includes one or more of hydroxyl, carboxyl, carbonyl, epoxy, ether, and ester groups; the oxygen-containing functional group is introduced into the carbon-based conductive framework through one or more of acid oxidation, thermal oxidation, plasma oxidation, electrochemical oxidation, ozone oxidation, and peroxide oxidation.
[0013] Furthermore, the oxidized carbon-based conductive framework exhibits an electronic conductivity of 10–150 S·cm under 20 MPa compaction conditions. -1 Furthermore, the electronic conductivity of the oxidized carbon-based conductive framework is 20% to 80% of the electronic conductivity of the carbon-based conductive framework before oxidation modification.
[0014] Furthermore, after mixing the hybrid conductor layer material with the Li6PS5Cl sulfide solid electrolyte at a mass ratio of 1:3, a two-dimensional... 7 Li -7 The lithium-ion exchange relaxation time obtained by Li-exchange NMR spectroscopy is no higher than 300 μs.
[0015] Furthermore, based on the total mass of the hybrid conductor layer, the content of the alloyed deposition acceptor component is 1 wt.% to 40 wt.%.
[0016] Furthermore, the hybrid conductor layer includes, along its thickness direction, an electron-damping lithium-ion exchange region near the sulfide solid electrolyte layer and an alloyed deposition acceptor region near the negative electrode current collector; the content of the alloyed deposition acceptor component on the side near the negative electrode current collector is higher than that on the side near the sulfide solid electrolyte layer.
[0017] A method for preparing a lithium deposition redirected hybrid conductor layer, the method comprising the following steps: S1. The carbon-based conductive material is oxidized to obtain an oxidized carbon-based conductive framework containing oxygen-containing functional groups. S2. Contact the oxidized carbon-based conductive framework with a metal salt precursor, metal nanoparticle, or metal compound precursor containing Ag, In, Zn, Sn, or Al. S3. Through coordination adsorption-in-situ reduction, mechanochemical anchoring or in-situ conversion treatment, alloyed deposit acceptor components are formed or fixed in the oxidized modified carbon-based conductive framework. S4. Mix the mixed conductor layer material with a binder and / or solvent to form a slurry, and coat the slurry onto the surface of the negative electrode current collector. After drying, a negative electrode current collector with the above-mentioned mixed conductor layer can be obtained.
[0018] A lithium metal battery includes a positive electrode, a sulfide solid electrolyte layer, a negative electrode current collector, and a mixed conductor layer; the mixed conductor layer is located between the sulfide solid electrolyte layer and the negative electrode current collector; the sulfide solid electrolyte layer includes Li6PS5Cl, Li3PS4, and Li7P3S. 11 Li 10 GeP2S 12 Li 10 SnP2S 12 Li 9.5 4Si 1.74 P 1.44 S 11.7 Cl 0.3 One or more of them.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention transforms the traditional conductive interface layer into a hybrid conductor layer with functions of electronic damping, lithium-ion exchange, and alloying deposition acceptor, thus avoiding the problem of preferential deposition of lithium metal on the sulfide solid electrolyte side caused by a simple high electronic conductivity carbon layer.
[0020] 2. This invention uses oxygen-containing functional groups to coordinate and anchor metal ions and reduce them in situ, so that the alloyed deposition acceptor components are fixed on the surface or defect sites of the carbon oxide framework, which is different from the physical mixing of ordinary metal powder and carbon materials.
[0021] 3. The present invention uses layered coating, gradient coating or electric field-assisted deposition to enrich the alloyed deposition acceptor components on the side near the negative electrode current collector, thereby redirecting the lithium deposition sites in the layer thickness direction.
[0022] 4. The hybrid conductor layer proposed in this invention can reduce the physically irreversible lithium generated during the lithium metal deposition / stripping process, thereby improving the lithium metal utilization rate and the coulombic efficiency stability of solid-state lithium metal batteries.
[0023] 5. This invention is applicable to sulfide solid lithium metal batteries, electrodeless solid lithium metal batteries, and lithium metal storage solid batteries, and has strong structural adaptability and process scalability. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the structure of the solid-state lithium metal battery proposed in this invention; Figure 2 for Figure 1 A magnified schematic diagram of the local structure; Figure 3 This is a schematic diagram illustrating the mechanism of lithium deposition site regulation using a lithium deposition redirection hybrid conductor layer proposed in this invention; Figure 4 This is a schematic diagram comparing the lithium deposition sites of the present invention and the prior art; Figure 5 This is a schematic diagram showing the X-ray photoelectron spectra and elemental analysis results of the oxidized carbon-based conductive frameworks in Comparative Examples 6-10. Figure 6 The image shows a scanning electron microscope (SEM) image and elemental distribution map of the negative electrode section after lithium metal pre-deposition in Comparative Example 5 when a TMG carbon-based interface layer is used. Figure 7 The image shows a scanning electron microscope (SEM) image and elemental distribution map of the negative electrode section after lithium metal pre-deposition in Comparative Example 10 when an OTMG carbon oxide interface layer is used. Figure 8 The images shown are scanning electron microscope images and elemental distribution maps of the negative electrode cross-section after lithium metal pre-deposition in Example 1 when using OTMG-Ag electronically damped lithium deposition redirected hybrid conductor layer. Figure 9 This is a schematic diagram comparing the negative electrode coulombic efficiency cycle test results of solid-state lithium metal batteries assembled with different interface layers in the comparative examples and embodiments. Figure 10 This is a comparative schematic diagram showing the proportion of physically irreversible lithium in solid-state lithium metal batteries assembled with different interface layers in the comparative examples and embodiments. Detailed Implementation
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] It should be noted that in the description of this invention, the terms "upper", "lower", "top", "bottom", "one side", "the other side", "left", "right", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not mean that the device or element must have a specific orientation, or be constructed and operated in a specific orientation.
[0027] The present invention proposes a lithium deposition redirected hybrid conductor layer for use between a sulfide solid electrolyte layer and a negative electrode current collector, such as... Figure 1 As shown, it is used to redirect the lithium metal deposition behavior on the negative electrode side; the hybrid conductor layer includes an oxidized carbon-based conductive framework and an alloyed deposition acceptor component.
[0028] The oxidized carbon-based conductive framework contains oxygen-containing functional groups, including one or more of hydroxyl, carboxyl, carbonyl, epoxy, ether, and ester groups. The oxygen-containing functional groups are introduced into the carbon-based conductive framework through one or more of acid oxidation, thermal oxidation, plasma oxidation, electrochemical oxidation, ozone oxidation, and peroxide oxidation.
[0029] Oxygen-containing functional groups can regulate the electron transport and lithium-ion transport capabilities of the carbon-based conductive framework, and improve the lithium-ion exchange capacity between the hybrid conductor layer and the sulfide solid electrolyte, thereby creating a structural environment in the thickness direction of the hybrid conductor layer that is conducive to the transport of lithium ions to the negative electrode current collector side.
[0030] The alloying deposition acceptor component includes one or more of Ag, In, Zn, Sn, and Al, and / or an oxide, fluoride, chloride, or sulfide of at least one of Ag, In, Zn, Sn, and Al; the alloying deposition acceptor component is generated in an oxidized carbon-based conductive framework through oxygen-containing functional group coordination anchoring, in-situ reduction, or in-situ transformation; the metal compound undergoes a transformation reaction during lithium deposition and generates in-situ a metal phase that can form an alloy with lithium.
[0031] The alloyed deposition acceptor component can provide deposition acceptor sites that can alloy with lithium, reducing the deposition resistance of lithium metal inside the hybrid conductor layer or near the negative electrode current collector.
[0032] The oxidized carbon-based conductive framework and the alloyed deposition acceptor components form a spatially matched structure of electron transport, lithium ion transport and alloying deposition sites in the thickness direction of the mixed conductor layer, so that lithium metal is preferentially deposited on the side closer to the negative electrode current collector during charging.
[0033] The carbon-based conductive framework includes one or more of the following: conductive carbon black, carbon nanotubes, graphitized carbon, porous carbon, hard carbon, soft carbon, graphene, and carbon fiber.
[0034] The conductive carbon black includes one or more of the following: TMG (super high conductivity carbon), SP (super carbon black), KJB (Kejtien black), VXC (Cabot conductive carbon), and MWCNT (multi-walled carbon nanotubes).
[0035] The oxidized carbon-based conductive framework exhibits an electronic conductivity of 10–150 S·cm under 20 MPa compaction conditions. -1 The preferred value is 20~100 S·cm. -1 Furthermore, the electronic conductivity of the oxidized carbon-based conductive framework is 20% to 80% of the electronic conductivity of the carbon-based conductive framework before oxidation modification, preferably 30% to 60%.
[0036] In this invention, the content of the alloyed deposition acceptor component is 1 wt.% to 40 wt.% based on the total mass of the mixed conductor layer; preferably, the content of the alloyed deposition acceptor component is 5 wt.% to 20 wt.%.
[0037] The hybrid conductor layer includes, along its thickness, an electron-damping lithium-ion exchange region near the sulfide solid electrolyte layer and an alloyed deposition acceptor region near the negative electrode current collector; the content of the alloyed deposition acceptor component is higher on the side near the negative electrode current collector than on the side near the sulfide solid electrolyte layer. Through the synergistic effect of the oxidized carbon-based conductive framework and the alloyed deposition acceptor component, the hybrid conductor layer can regulate electron transport, lithium-ion transport, and alloying deposition behavior along the thickness direction.
[0038] After lithium metal pre-deposition, along the thickness direction of the mixed conductor layer, lithium metal is mainly distributed on the side closer to the negative electrode current collector, and the amount of lithium deposited on the side closer to the negative electrode current collector is higher than the amount of lithium deposited on the side closer to the sulfide solid electrolyte layer.
[0039] The hybrid conductor layer material was mixed with Li6PS5Cl sulfide solid electrolyte at a mass ratio of 1:3, and then a two-dimensional... 7 Li -7 The lithium-ion exchange relaxation time obtained by Li-exchange NMR spectroscopy is no higher than 300 μs, preferably 50~200 μs.
[0040] like Figure 2 The diagram illustrates the working mechanism of the aforementioned hybrid conductor layer. The oxidized carbon-based conductive framework primarily regulates the electron transport intensity and lithium-ion exchange capacity within the layer, while the alloyed deposition acceptor component provides lithium alloying deposition sites. Together, they create a spatially matched structure of electron transport, lithium-ion transport, and alloying deposition sites along the thickness direction of the hybrid conductor layer, thereby preferentially depositing lithium metal on the side closest to the negative electrode current collector. Figure 3 As shown, without the hybrid conductor layer of this invention, lithium metal is deposited on the sulfide solid electrolyte side. With the hybrid conductor layer of this invention, lithium metal is preferentially deposited between the negative electrode current collector and the hybrid conductor layer.
[0041] The hybrid conductor layer described in this invention does not simply reduce electronic conductivity, nor does it merely increase lithium-ion transport capability. Instead, it simultaneously adjusts electronic conductivity and lithium-ion exchange capability to a transport matching window suitable for lithium deposition site redirection. Specifically, the electronic conductivity of the oxidized carbon-based conductive framework under 20 MPa compaction conditions can be 10~150 S·cm. -1Furthermore, the electronic conductivity is lower than that of the carbon-based conductive framework before oxidation modification; simultaneously, the lithium-ion exchange relaxation time between the hybrid conductor layer material and the Li6PS5Cl sulfide solid electrolyte is no higher than 300 μs. Within this transport matching window, the hybrid conductor layer can avoid excessive electron enrichment on the sulfide solid electrolyte side while maintaining rapid lithium-ion exchange, and induce preferential deposition of lithium metal near the negative electrode current collector through alloying deposition acceptor components.
[0042] All operations involving the assembly of sulfide solid electrolytes and solid batteries were performed in an argon glove box, where the water and oxygen content were both below 0.1 ppm.
[0043] A method for preparing a lithium deposition redirected hybrid conductor layer, the method comprising the following steps: S1. The carbon-based conductive material is oxidized to obtain an oxidized carbon-based conductive framework containing oxygen-containing functional groups. S2. Contact the oxidized carbon-based conductive framework with a metal salt precursor, metal nanoparticle, or metal compound precursor containing Ag, In, Zn, Sn, or Al. S3. Through coordination adsorption-in-situ reduction, mechanochemical anchoring or in-situ conversion treatment, alloyed deposit acceptor components are formed or fixed in the oxidized modified carbon-based conductive framework. S4. Mix the mixed conductor layer material with a binder and / or solvent to form a slurry, and coat the slurry onto the surface of the negative electrode current collector. After drying, a negative electrode current collector with the above-mentioned mixed conductor layer can be obtained.
[0044] The hybrid conductor layer is formed by layer coating, gradient coating or electric field-assisted deposition, such that the content of the alloyed deposition acceptor component is higher on the side near the negative electrode current collector than on the side near the sulfide solid electrolyte layer.
[0045] The metal salt precursor includes one or more of nitrates, chlorides, acetates, or organometallic salts; the reduction treatment includes one or more of ascorbic acid reduction, borohydride reduction, hydrogen reduction, thermal reduction, or electrochemical reduction.
[0046] A lithium metal battery includes a positive electrode, a sulfide solid electrolyte layer, a negative electrode current collector, and a hybrid conductor layer thereof; the hybrid conductor layer is located between the sulfide solid electrolyte layer and the negative electrode current collector, and is used to induce preferential deposition of lithium metal on the side closer to the negative electrode current collector during charging; the sulfide solid electrolyte layer includes Li6PS5Cl, Li3PS4, and Li7P3S. 11 Li 10 GeP2S 12 Li 10 SnP2S 12Li 9.5 4Si 1.74 P 1.44 S 11.7 Cl 0.3 One or more of the following. Preferably, the sulfide solid electrolyte layer comprises Li6PS5Cl.
[0047] The present invention will be further illustrated below through specific embodiments and comparative examples: Example 1 This embodiment provides a coordination-anchored-in-situ reduced OTMG-Ag electron-damped lithium deposition redirected hybrid conductor layer. The preparation method is as follows: Weigh 1.00 g of TMG carbon material and add it to 80 mL of 6 mol•L⁻¹. -1 The reaction was carried out in nitric acid solution with stirring at 80 °C for 6 h. After the reaction was completed, the obtained solid product was centrifuged and washed successively with deionized water and ethanol until the washing solution was nearly neutral. Then, it was vacuum dried at 80 °C for 12 h to obtain oxidized modified TMG, denoted as OTMG.
[0048] Weigh 90 mg of OTMG and disperse it in 20 mL of ethanol / water mixture. Add the equivalent of 10 mg of silver nitrate precursor (Ag) and stir for 2 hours to allow Ag to react. + Ag undergoes coordination adsorption with oxygen-containing functional groups such as carboxyl, hydroxyl, and carbonyl groups on the surface of OTMG. Subsequently, ascorbic acid reducing agents or borohydride reducing agents are added to reduce Ag... + Ag nano-deposit acceptor sites were generated in situ on the surface of OTMG by reduction. After the reaction, the material was washed and vacuum dried at 60°C for 12 h to obtain a coordinated anchored OTMG-Ag hybrid conductor layer material.
[0049] Through XPS or elemental analysis, the oxygen content of OTMG in this embodiment is 1.8 wt.%, which is within the preferred range of 0.5 wt.% to 5 wt.%.
[0050] The OTMG-Ag hybrid conductor layer material and PVDF binder were mixed at a mass ratio of 90:10, and an appropriate amount of N-methylpyrrolidone was added to form a first slurry. The first slurry was then coated onto the surface of the copper foil negative electrode current collector. After vacuum drying at 80°C for 12 hours, an alloyed deposition acceptor region was formed near the negative electrode current collector side.
[0051] OTMG and PVDF binder were mixed at a mass ratio of 90:10, and an appropriate amount of N-methylpyrrolidone was added to form a second slurry. This second slurry was coated onto the surface of the alloyed deposition acceptor region, forming an electron-damping lithium-ion exchange region near the sulfide solid electrolyte layer. After vacuum drying at 80°C for 12 hours, an OTMG-Ag hybrid conductor layer with a thickness-direction spatially matched structure was obtained.
[0052] In this embodiment, the content of Ag is 10 wt.% based on the total mass of OTMG and Ag. In other embodiments, the content of the alloying deposition acceptor component can be 1 wt.% to 40 wt.%; preferably, the content of the alloying deposition acceptor component is 5 wt.% to 20 wt.%.
[0053] Examples 2-5 Examples 2-5 provide mixed conductor layers containing different alloyed deposition acceptor components. Ag, In, Zn, and Sn can be obtained through metal salt coordination adsorption-in-situ reduction; Al can be obtained through Al nanoparticle mechanochemical anchoring. The remaining oxidation modification conditions, layer coating methods, and drying conditions are the same as in Example 1.
[0054] In Example 2, the metal salt precursor is indium salt, and the alloying deposition acceptor component is In, resulting in an OTMG-In hybrid conductor layer.
[0055] In Example 3, the metal salt precursor was zinc salt, and the alloying deposition acceptor component was Zn, resulting in an OTMG-Zn mixed conductor layer.
[0056] In Example 4, the metal salt precursor was tin salt, and the alloying deposition acceptor component was Sn, resulting in an OTMG-Sn hybrid conductor layer.
[0057] In Example 5, the alloyed deposition acceptor component is Al, which is combined with OTMG in the form of Al nanoparticles through mechanochemical treatment, ultrasonic dispersion or surface anchoring to obtain an OTMG-Al hybrid conductor layer.
[0058] In the above embodiments, OTMG is used to adjust the electron transport intensity and lithium-ion exchange capacity in the hybrid conductor layer, while Ag, In, Zn, Sn, or Al are used to provide lithium alloying deposition acceptor sites. The two elements form a spatial match between electron transport, lithium-ion transport, and alloying deposition sites along the thickness direction of the hybrid conductor layer, causing lithium metal to preferentially distribute on the side closer to the negative electrode current collector during deposition.
[0059] Example 6 This embodiment provides a self-activated in-situ conversion type OTMG-ZnO hybrid conductor layer. The difference between this embodiment and Embodiment 1 is that the silver nitrate precursor is replaced with ZnO nanoparticles or zinc oxide precursor. The rest of the composite method, film formation method and drying conditions are the same as in Embodiment 1.
[0060] During the initial lithium deposition process, ZnO can undergo a transformation reaction, generating an in-situ Zn phase that can alloy with lithium, and forming an inorganic interface component. Thus, the OTMG-ZnO hybrid conductor layer can induce preferential lithium metal deposition on the side closer to the negative electrode current collector through the synergistic effect of the oxidized carbon-based conductive framework and the in-situ generated alloyed deposition acceptor component.
[0061] In other embodiments, the hybrid conductor layer can also be formed by electric field-assisted deposition. OTMG and coordinated anchored OTMG-Ag hybrid conductor layer materials are dispersed in an electrophoretic deposition solution, and a copper foil negative electrode current collector is used as the deposition electrode. Under the action of an applied electric field, the hybrid conductor layer material is deposited on the surface of the copper foil.
[0062] Comparative Examples 1-5 Comparative Examples 1-5 provide original carbon material interface layers to illustrate the effect of unoxidized carbon material as an interface layer on lithium deposition behavior.
[0063] Weigh 90 mg of carbon material and 10 mg of PVDF binder, add them to an appropriate amount of N-methylpyrrolidone, and stir for 6 h to form a uniform slurry. Coat the obtained slurry onto the surface of the copper foil negative electrode current collector, with a wet film thickness of 50 μm, and vacuum dry at 80 °C for 12 h to obtain the original carbon material interface layer.
[0064] Comparative Example 1 uses KJB; Comparative Example 2 uses VXC; Comparative Example 3 uses SP; Comparative Example 4 uses MWCNT; Comparative Example 5 uses TMG.
[0065] The aforementioned original carbon material interface layer can provide an electron transport network and some structural support, but it has not undergone oxidation modification or introduced alloying deposition acceptor components, making it difficult to achieve spatial matching of electron transport, lithium-ion transport, and alloying deposition sites along the layer thickness direction. Taking the TMG interface layer of Comparative Example 5 as an example, the cross-sectional scanning electron microscope results after lithium metal pre-deposition are as follows... Figure 5 As shown, lithium metal is deposited primarily from the side closest to the sulfide solid electrolyte layer.
[0066] Comparative Examples 6-10 Comparative Examples 6-10 provide carbon oxide material interface layers to illustrate the effect of individual oxidation modification on the electron transport capability and lithium-ion exchange capability of the carbon-based conductive framework.
[0067] Taking OTMG in Comparative Example 10 as an example, its preparation method is the same as that of OTMG in Example 1. The only difference between Comparative Examples 6-9 and Comparative Example 10 is that TMG is replaced with KJB, VXC, SP and MWCNT respectively, while the other oxidation modification conditions and interface layer preparation conditions are the same.
[0068] Comparative Example 6 yields the OKJB interface layer; Comparative Example 7 yields the OVXC interface layer; Comparative Example 8 yields the OSP interface layer; Comparative Example 9 yields the OMWCNT interface layer; Comparative Example 10 yields the OTMG interface layer.
[0069] After oxidation modification, oxygen-containing functional groups such as hydroxyl, carboxyl, carbonyl, and epoxy groups are introduced into the surface and / or defect sites of the carbon-based conductive framework. Figure 4 The X-ray photoelectron spectroscopy and elemental analysis results of the oxidatively modified carbon-based conductive framework are used to illustrate that oxidative modification can introduce oxygen-containing functional groups into the carbon-based conductive framework.
[0070] It should be noted that the carbon oxide material interface layer can regulate electron transport capability and improve lithium-ion exchange capability with sulfide solid electrolyte, but it does not include alloyed deposit acceptor components. Therefore, in this invention, it is used as a comparative example to illustrate the role of carbon-based conductive framework modified by oxidation alone.
[0071] The following tests were performed on the above embodiments and comparative examples: 1. Electron conductivity and lithium-ion exchange relaxation time test The electronic conductivity of carbon-based materials before and after oxidation modification was tested using a powder resistivity meter. During the test, the powder material to be tested was placed in a test mold, and its electronic conductivity was measured under a compaction pressure of 20 MPa.
[0072] Using two-dimensional Li 7 Lithium-ion exchange relaxation time was measured using exchange nuclear magnetic resonance (NMR) spectroscopy to determine the lithium-ion exchange relaxation time between different carbon-based materials or hybrid conductor layer materials and Li6PS5Cl sulfide solid electrolyte. During testing, the test material and Li6PS5Cl were mixed at a mass ratio of 1:3, ground uniformly, and then the test was performed. A shorter lithium-ion exchange relaxation time indicates a faster lithium-ion exchange between the material and the sulfide solid electrolyte.
[0073] The electronic conductivity test results are shown in Table 1, and the lithium-ion exchange relaxation time test results are shown in Table 2.
[0074] Table 1. Electronic conductivity of different carbon-based conductive frameworks before and after oxidation modification
[0075] As shown in Table 1, the electronic conductivity of KJB, VXC, SP, MWCNT and TMG all decreased after oxidation modification, indicating that oxidation modification can dampen the electron transport capability of the carbon-based conductive framework and prevent excessive concentration of electron transport within the interface layer.
[0076] Table 2. Lithium-ion exchange relaxation times of different carbon-based materials or electronically damped lithium-deposited redirected hybrid conductor layers.
[0077] As shown in Table 2, oxidation modification can significantly shorten the lithium-ion exchange relaxation time between the carbon-based material and the Li6PS5Cl sulfide solid electrolyte. Further introduction of alloyed deposition acceptor components maintains a relatively fast lithium-ion exchange capacity in the mixed conductor layer, which is beneficial for forming a transport environment suitable for lithium deposition site redirection between the sulfide solid electrolyte layer and the negative electrode current collector.
[0078] 2. Electrochemical performance and lithium deposition site testing The interface layer to be tested was deposited on the surface of the negative electrode current collector, and a solid-state half-cell was assembled with a Li6PS5Cl sulfide solid electrolyte layer and a lithium metal counter electrode. At 1 mA•cm -2 Lithium deposition / stripping tests were conducted at current density, with a single deposition capacity of 5 mAh•cm³. -2 Record the initial Coulomb efficiency and the average Coulomb efficiency during the cycle.
[0079] The solid-state battery after lithium metal pre-deposition was disassembled, and the negative electrode structure was removed. The lithium metal deposition location was observed using cross-sectional scanning electron microscopy and elemental distribution analysis. Physically irreversible lithium was quantitatively analyzed by gas chromatography. The test results are shown in Table 3.
[0080] Table 3. Coulombic efficiency and percentage of physically irreversible lithium in solid-state lithium metal batteries assembled with different interface layers.
[0081] As shown in Table 3, compared with Comparative Examples 5 and 10, the hybrid conductor layers in Examples 1-5 all exhibited higher cycle coulombic efficiency and lower physically irreversible lithium content, such as... Figure 8 and Figure 9 As shown, although Comparative Example 10 has a better lithium-ion exchange capacity, its average coulombic efficiency is still lower than that of Examples 1-5 due to the lack of alloyed deposition acceptor components.
[0082] Figure 5 The image shows a cross-sectional scanning electron microscope (SEM) image and elemental distribution of the negative electrode with a TMG carbon-based interface layer after lithium metal pre-deposition in Comparative Example 5. Figure 5 As shown, after adopting the TMG interface layer, lithium metal begins to deposit from the solid electrolyte side, causing damage to the solid electrolyte layer interface. This indicates that the unoxidized carbon interface layer cannot effectively induce the lithium deposition sites to shift to the negative electrode current collector side.
[0083] Figure 6 The image shows a cross-sectional scanning electron microscope (SEM) image and elemental distribution of the negative electrode with an OTMG carbon oxide interface layer after lithium metal pre-deposition in Comparative Example 10. Figure 6As shown, after using the OTMG interface layer, lithium metal still mainly deposits from the solid electrolyte side. This indicates that although the carbon interface layer treated by oxidation alone provides good lithium-ion exchange capacity, it is still difficult to stably induce the transfer of lithium deposition sites to the negative electrode current collector side due to the lack of alloyed deposition acceptor components.
[0084] Figure 7 The images show the cross-sectional scanning electron microscope (SEM) image and elemental distribution map of the negative electrode using an OTMG-Ag hybrid conductor layer after lithium metal pre-deposition in Example 1. Figure 7 As shown, after using the OTMG-Ag hybrid conductor layer, lithium metal is mainly deposited on the side closer to the negative electrode current collector, indicating that the hybrid conductor layer of the present invention can effectively redirect the lithium deposition site, causing the lithium metal deposition site to shift from the side closer to the sulfide solid electrolyte layer to the side closer to the negative electrode current collector.
[0085] The above results indicate that the hybrid conductor layer provided by the present invention is not simply a superposition of carbon materials and alloyed metals, but rather adjusts the spatial matching relationship of electron transport, lithium ion transport and alloyed deposition sites in the layer thickness direction through the synergistic effect between the oxidized modified carbon-based conductive framework and the alloyed deposition acceptor components, so that the lithium metal deposition sites shift from the side closer to the sulfide solid electrolyte layer to the side closer to the negative electrode current collector.
[0086] Although the above embodiments primarily use OTMG as the oxidized carbon-based conductive framework and Ag, In, Zn, Sn, and Al as alloying deposition acceptor components for illustration, the present invention is not limited thereto. In other embodiments, the oxidized carbon-based conductive framework may also be one or more of the following: oxidized conductive carbon black, oxidized carbon nanotubes, oxidized porous carbon, oxidized graphitized carbon, oxidized hard carbon, oxidized soft carbon, oxidized graphene, or oxidized carbon fiber.
[0087] The alloying deposition acceptor component may also be one or more of Ag, In, Zn, Sn, Al, Mg, Bi, Si, and Ge, or one or more of the oxides, fluorides, chlorides, sulfides, nitrates, carbonates, phosphates, and organometallic salts of the above metals.
[0088] Sulfide solid electrolytes may include Li6PS5Cl, Li3PS4, and Li7P3S 11 Li 10 GeP2S 12 Li 10 SnP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3One or more of the following. The hybrid conductor layer can be used in lithium metal anode solid-state batteries, anode-free solid-state lithium metal batteries, or lithium metal storage solid-state batteries.
[0089] Matters not covered in this invention are common knowledge.
[0090] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A lithium-deposited redirected hybrid conductor layer, characterized in that: The hybrid conductor layer is used to be disposed between the sulfide solid electrolyte layer and the negative electrode current collector; the hybrid conductor layer includes an oxidized modified carbon-based conductive framework and an alloyed deposited acceptor component; The oxidized carbon-based conductive framework contains oxygen-containing functional groups. The alloyed deposition acceptor component includes one or more of Ag, In, Zn, Sn, and Al, and / or an oxide, fluoride, chloride, or sulfide of at least one of Ag, In, Zn, Sn, and Al; the alloyed deposition acceptor component is generated in an oxidized carbon-based conductive framework through oxygen-containing functional group coordination anchoring, in-situ reduction, or in-situ transformation. The oxidized carbon-based conductive framework and the alloyed deposition acceptor components form a spatially matched structure for electron transport, lithium-ion transport, and alloyed deposition sites in the thickness direction of the mixed conductor layer. The oxidized carbon-based conductive framework exhibits an electronic conductivity of 10–150 S·cm under 20 MPa compaction conditions. -1 Furthermore, the electronic conductivity of the oxidized carbon-based conductive framework is 20% to 80% of the electronic conductivity of the carbon-based conductive framework before oxidation modification. The hybrid conductor layer material was mixed with Li6PS5Cl sulfide solid electrolyte at a mass ratio of 1:3, and then a two-dimensional... 7 Li -7 The lithium-ion exchange relaxation time obtained by Li-exchange NMR spectroscopy is no higher than 300 μs; The hybrid conductor layer includes, along its thickness direction, an electron-damping lithium-ion exchange region near the sulfide solid electrolyte layer and an alloyed deposition acceptor region near the negative electrode current collector; the content of the alloyed deposition acceptor component on the side near the negative electrode current collector is higher than that on the side near the sulfide solid electrolyte layer.
2. The lithium deposition redirected hybrid conductor layer according to claim 1, characterized in that: The carbon-based conductive framework includes one or more of conductive carbon black, carbon nanotubes, graphene, and carbon fibers.
3. The lithium deposition redirected hybrid conductor layer according to claim 2, characterized in that: The conductive carbon black includes one or more of the following: super high conductivity carbon, super carbon black, Ketjen black, and Cabot conductive carbon.
4. The lithium deposition redirected hybrid conductor layer according to claim 3, characterized in that: The oxygen-containing functional group includes one or more of hydroxyl, carboxyl, carbonyl, ether, and ester groups; the oxygen-containing functional group is introduced into the carbon-based conductive framework through one or more of acid oxidation, thermal oxidation, plasma oxidation, electrochemical oxidation, ozone oxidation, and peroxide oxidation.
5. The lithium deposition redirected hybrid conductor layer according to claim 1, characterized in that: The content of the alloyed deposition acceptor component is 1 wt.% to 40 wt.% based on the total mass of the hybrid conductor layer.
6. A method for preparing a lithium deposition redirected hybrid conductor layer as described in claim 1, characterized in that, The method includes the following steps: S1. The carbon-based conductive material is oxidized to obtain an oxidized carbon-based conductive framework containing oxygen-containing functional groups. S2. Contact the oxidized carbon-based conductive framework with a metal salt precursor, metal nanoparticle, or metal compound precursor containing Ag, In, Zn, Sn, or Al. S3. Through coordination adsorption-in-situ reduction, mechanochemical anchoring or in-situ conversion treatment, alloyed deposit acceptor components are formed or fixed in the oxidized modified carbon-based conductive framework. S4. Mix the mixed conductor layer material with a binder and / or solvent to form a slurry, and coat the slurry onto the surface of the negative electrode current collector. After drying, a negative electrode current collector with the above-mentioned mixed conductor layer can be obtained.
7. A lithium metal battery, implemented using the hybrid conductor layer of claim 1, characterized in that: The battery includes a positive electrode, a sulfide solid electrolyte layer, a negative electrode current collector, and a mixed conductor layer; the mixed conductor layer is located between the sulfide solid electrolyte layer and the negative electrode current collector; the sulfide solid electrolyte layer includes Li6PS5Cl, Li3PS4, and Li7P3S. 11 Li 10 GeP2S 12 Li 10 SnP2S 12 Li 9.5 4Si 1.74 P 1.44 S 11.7 Cl 0.3 One or more of them.
Citation Information
Patent Citations
Solid-state battery, negative pole piece and preparation method of negative pole piece
CN120709299A
Alloyed composite current collector, preparation method thereof and solid-state battery
CN122091600A